2021
DOI: 10.1007/jhep01(2021)025
|View full text |Cite
|
Sign up to set email alerts
|

A 4d $$ \mathcal{N} $$ = 1 Cardy Formula

Abstract: We study the asymptotic behavior of the (modified) superconformal index for 4d $$ \mathcal{N} $$ N = 1 gauge theory. By considering complexified chemical potential, we find that the ‘high-temperature limit’ of the index can be written in terms of the conformal anomalies 3c − 2a. We also find macroscopic entropy from our asymptotic free energy when the Hofman-Maldacena bound 1/2 < a/c < 3/2 for the interacting SCFT is satisfied. We study $$ \mathcal{N} $$ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
127
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(139 citation statements)
references
References 65 publications
(127 reference statements)
12
127
0
Order By: Relevance
“…There are only gauge and mixed CS terms on S 3 . After integrating over S 3 , we obtain the following results, It is exactly the same with the Cardy formula given in [37,38] JHEP02(2021)092…”
Section: A a 4d N = 1 Cardy Formulamentioning
confidence: 62%
See 3 more Smart Citations
“…There are only gauge and mixed CS terms on S 3 . After integrating over S 3 , we obtain the following results, It is exactly the same with the Cardy formula given in [37,38] JHEP02(2021)092…”
Section: A a 4d N = 1 Cardy Formulamentioning
confidence: 62%
“…In this section, we reproduce a 4d N = 1 Cardy formula found in [37,38] by following our anomaly-based approach. We consider the following superconformal index of a 4d N = 1 theory,…”
Section: A a 4d N = 1 Cardy Formulamentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it was demonstrated that the index can indeed detect the phase structure, thereby accounting for the entropy of large AdS black holes [27][28][29]. The Cardy-like formula for the 4d index [30,31] describing the high-energy behavior suggests that our model is unlikely to exhibit such a phase transition. However, it would be desirable to study detailed phase structure of our theory using the superconformal index, as was done in [28,32,33].…”
Section: Jhep05(2021)124mentioning
confidence: 94%